Enantioselective Copper‐Catalyzed Formal [2+1] and [4+1] Annulations of Diynes with Ketones via Carbonyl Ylides - Qi, Lin‐Jun; Li, Cui‐Ting; Huang, Zheng‐Qi; Jiang, Jia‐Tian; Zhu, Xin‐Qi; Lu, Xin; Ye, Long‐Wu (Angewandte Chemie, 2022)
Carbonyl ylides have proven to be powerful synthons for the efficient construction of various valuable O‐heterocycles, and the formation of carbonyl ylides by the reaction of metal carbenes with carbonyls has attracted increasing attention over the past decades. However, a catalyst‐controlled highly enantioselective reaction of carbonyl ylides from metal carbenes is extremely challenging. Herein, we report a novel copper‐catalyzed asymmetric formal [2+1] and [4+1] annulations of diynes with ketones via carbonyl ylides. Importantly, this protocol not only represents the first example of successful asymmetric epoxidation via carbonyl ylides, but also constitutes the first reaction of vinyl cations with carbonyl compounds. This method leads to the divergent, practical and atom‐economical synthesis of a range of chiral oxiranes and dihydrofurans in moderate to excellent yields with generally excellent enantioselectivities and diastereoselectivities via remote‐stereocontrol strategy. A copper‐catalyzed asymmetric formal [2+1] and [4+1] annulations of diynes with ketones via carbonyl ylides is disclosed. This protocol enables the divergent, practical and atom‐economical synthesis of a range of chiral oxiranes and dihydrofurans in moderate to excellent yields with generally excellent enantioselectivities and diastereoselectivities.